Primula qiupuensis, a new species in Primulaceae from China - Zhang, Chao; Zhang, Jian-Ye; Chen, Fang-Ming; Chen, Wen-Hao; Chen, Dong-Sheng; Shao, Jian-Wen (Phytotaxa, 2020)
Primula qiupuensis J.W.Shao, a new species in sect. Ranunculoides from eastern China, is described and illustrated. It can be distinguished from relative species within the section by corolla lobe apex rounded and pollen grains suboblate and stephanocolpate. Primula qiupuensis is endemic to the hilly and mountainous areas of Qiupu River Basin in Anhui Province.